Illusory sentience: imaginations of AI in history - Ng, Jazreel Wen Shin (Nanyang Technological University, 2024)
Today, machines can not only calculate with astonishing speed, but also decipher languages, recognise faces, and even engage in conversations with humans. The capabilities of AI have exceeded imaginations of the past and manifested into tangible and transformative forces in our daily lives. Though these advancements have provided us with convenience, they have also issued a new series of problems. Popular culture in the past century have depicted themes of how rapid AI development could lead to dire circumstances for the human creators. Indeed, beyond the technicalities of creating a machine that can think, there also lies a cascade of social and cultural discourses behind AI development. It is thus imperative for us to trace the history of AI development; to look at the core moments where the technological, social and cultural histories of AI intersect. As such, this paper seeks to investigate how society perceives AI development and how this has changed over time. It seeks to answer the question: how have the capabilities and imaginations of AI changed in the past century? I argue that the increasingly persuasive nature of AI to seem ‘sentient’, due to technological advancement, transforms social imaginations and perspectives of AI’s role in society.